2018
DOI: 10.2334/josnusd.17-0206
|View full text |Cite
|
Sign up to set email alerts
|

The effects of adding various ratios of zirconium oxide nanoparticles to poly(methyl methacrylate) on physical and mechanical properties

Abstract: Abstract:The aim of the present study is to evaluate the transverse strength, modulus of elasticity, surface roughness, hardness, and water sorption/solubility of nanoparticle zirconium oxide (nano-ZrO 2 ) added to heat-cured poly(methyl methacrylate) (PMMA) after thermocycling. The specimens were divided into four groups according to the ratio of nano-ZrO 2 addition to heat-cured PMMA; group 1: 5% nano-ZrO 2 ; group 2: 10% nano-ZrO 2 ; group 3: 20% nano-ZrO 2 , and group 4 (control): PMMA without nano-ZrO 2 .… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
48
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(58 citation statements)
references
References 30 publications
8
48
1
1
Order By: Relevance
“…This problem may lead to decreased chemical interaction between the particles and the polymeric matrix [84]. The inhomogeneities in materials act as structural defects causing stress concentrations and strength reduction [85,86]. This corresponds well with the results of SEM observations (Figures 4 and 6) which showed the changes of morphologies of fractured samples and more brittle behavior of the composites.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…This problem may lead to decreased chemical interaction between the particles and the polymeric matrix [84]. The inhomogeneities in materials act as structural defects causing stress concentrations and strength reduction [85,86]. This corresponds well with the results of SEM observations (Figures 4 and 6) which showed the changes of morphologies of fractured samples and more brittle behavior of the composites.…”
Section: Discussionsupporting
confidence: 73%
“…Convergent results for PMMA denture base materials were obtained in other works for commercial and experimental materials [110][111][112][113]. Furthermore, Ergun et al [85] reported a two-fold increase in sorption and more than three-fold increase in solubility with increasing concentration of zirconium oxide nanoparticles introduced to PMMA denture base resin. The penetration of water or aqueous solutions into the material also has an impact on its properties, because acrylates can undergo slow degradation due to the fact of hydrolysis as well as enzymatic reactions [78] which affects cytotoxicity and tribological and mechanical properties [114,115].…”
Section: Discussionsupporting
confidence: 52%
“…Ergun et al investigated the effect of reinforcing conventional heat-cured PMMA with concentration of (5 wt.%, 10 wt.% and 20 wt.%) zirconia nanoparticles on water sorption and solubility after 28 days [31]. The findings showed that an increase in ZrO 2 concentration increased water sorption.…”
Section: Discussionmentioning
confidence: 99%
“…6 Zirconium oxide (ZrO 2 ) is a metal oxide that possesses several advantages such as good mechanical strength, fracture toughness, hardness, wear and chemical resistance and good thermal stability, thus making it beneficial for use in dental materials for reinforcement of denture base resins. 20 Several studies that incorporated zirconium dioxide (ZrO2) nanoparticles showed improvement in the mechanical properties of PMMA. 3,4,11,12,20-22. Titanium (Ti) and Ti-based alloys are the materials preferred in the production of implants for medical and dental applications due to their low toxicity, ease of availability, low cost, chemical stability, resistance to corrosion, good strength, high refractive index and biocompatibility.…”
Section: Discussion:-mentioning
confidence: 99%